Pengaruh Struktur Pasar Terhadap Profitabilitas Perbankan Syariah di Indonesia - Siti Yuhanah (Esensi: Jurnal Bisnis dan Manajemen, 2016)
The Impact of Market Structure to Profitability in The Indonesian Islamic Banking IndustryThe aim at the study to analyze the impact of market structure to the profitability of Islamic banking industry in Indonesia. The method of this research is panel regression with random effect. Data shown that Indonesian Islamic banking industry is highly concentrated, we can see the concentration ratio above 45%. The estimation result shown that the market structure –that proxied by market share- don’t have an impact on profitability in Indonesian Islamic banking industry. The control variables shown that only BOPO and NPF ratio that have an impact on profitability, otherwise the CAR and GDP growth don’t have an impact on profitability. This result shown that the SCP hypothesis didn’t happened at Indonesian Islamic banking industryDOI: 10.15408/ess.v6i1.3138